2012
DOI: 10.1039/c2cc32271d
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme-encapsulated microreactor for efficient theanine synthesis

Abstract: A flow-type microreactor containing glutaminase-mesoporous silica composites with 10.6 nm pore diameter (TMPS10.6) was developed for the continuous synthesis of theanine, a unique amino acid. High enzymatic activity was exhibited by the local control of the reaction temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 13 publications
0
27
0
1
Order By: Relevance
“…Soaking the support with liquid of comparable refractive index is a possible solution to enable direct measurements also in such cases [12,62,63]. Evidence from CLSM studies on the interaction of proteins with chromatographic supports can be translated almost directly to enzyme immobilization [50,62,[71][72][73][74][75][76][77][78][79][80][81][82][83]. Relationships between the dynamics of protein adsorption and the external and internal geometrical features of the support were established [84][85][86].…”
Section: Direct Visualization Of Protein Distribution In Solid-suppormentioning
confidence: 95%
“…Soaking the support with liquid of comparable refractive index is a possible solution to enable direct measurements also in such cases [12,62,63]. Evidence from CLSM studies on the interaction of proteins with chromatographic supports can be translated almost directly to enzyme immobilization [50,62,[71][72][73][74][75][76][77][78][79][80][81][82][83]. Relationships between the dynamics of protein adsorption and the external and internal geometrical features of the support were established [84][85][86].…”
Section: Direct Visualization Of Protein Distribution In Solid-suppormentioning
confidence: 95%
“…These variations in composition have a very strong impact on the acid and basic properties of solids. In the case of HAP-Ds, calcium deficiency causes a drop in basicity [145] and an increase of acidity [146]. In the case of HAP-Es, an increase of basicity [147] and a drop in acidity [144] could be generally observed.…”
Section: Dehydration Over Hydroxyapatitesmentioning
confidence: 99%
“…All these variations mainly concern site density, but a similar variations in site strength to a lesser extent can be also observed. Matsuura et al have studied the impact of the variation of the Ca/P ratio associated with the partial substitution of calcium by sodium [146,148], as well as the effect of the substitution of calcium by Pb or Sr and P by V [150] for HAPs prepared by hydrothermal synthesis. The authors obtains excellent yields (in the order of 70 %) of acrylic acid with the catalyst Ca-Na-HAP(1.55) (Ca/P = 1.55; (Ca+Na)/ P = 1.65), with a remarkable stability over time (Fig.…”
Section: Dehydration Over Hydroxyapatitesmentioning
confidence: 99%
“…Some recent articles, such as that of Matsuura et al, have reported enzyme-encapsulated microreactors for efficient synthesis. [21] Zhang et al used an open tubular microreactor with an enzyme-functionalized microfluidic channel for the amperometric detection of glucose. [22] The linear range for the detecMany oxidation processes require the presence of molecular oxygen in the reaction media.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, microchannels were packed with encapsulated enzymes and called "packed-bed micro-bioreactors." [21,23,24] In this paper, we demonstrate that a continuously operated microreactor system can be used for oxidative enzyme catalysis even without immobilization. For the appropriate test reaction, the biocatalyst should have high activity and a moderate price.…”
mentioning
confidence: 99%